Local Culture and The Risk of Pulmonary Tuberculosis: A Case Study in Teminabuan Community Health Center, Indonesia - Iskandar, Ishaq; Naolin, Imelda; Adam, Arlin; Iskandar, Harun; Syakri, Syamsuri (Diversity: Disease Preventive of Research Integrity, 2025)
Pulmonary tuberculosis (TB) remains a persistent public health challenge globally, with Indonesia ranking among the highest burden countries. In regions such as Southwest Papua, the incidence of TB is strongly influenced by cultural practices and daily behavioral patterns, yet limited studies have explored this dimension. This study aimed to analyze behavioral factors related to pulmonary TB incidence in Teminabuan, Indonesia, focusing on ventilation practices, cough etiquette, sputum disposal, smoking, and betel nut chewing. A cross-sectional design was conducted from May to June 2024 involving 97 respondents, consisting of families and neighbors of TB patients, selected through purposive sampling. The majority of participants were indigenous Papuans (76.29%), with 44.33% consuming betel nut and 43.33% spitting indiscriminately. Bivariate analysis showed that poor ventilation, inadequate cough etiquette, and indiscriminate spitting were significantly associated with TB incidence (p < 0.05). Among these, indiscriminate spitting was the most influential factor (PR = 0.421; 95% CI: 0.194–0.648). Smoking showed no significant association, while betel nut chewing, often accompanied by spitting, was found to increase TB transmission risk. These findings underscore the urgent need for culturally sensitive interventions that address traditional practices, while promoting the principle of cleanliness as part of faith in Islam, thereby strengthening family health protection and TB control efforts.